Jazz Babies Birmingham Royal Ballet at Sadler's Wells reviewed - Winship, Lyndsey (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Review of Birmingham Royal Ballet at Sadler's Wells. PALABRAS CLAVE: Such Sweet Thunder, David Bintley, Duke Ellington, Birmingham Royal Ballet, jazz, The Orpheus Suite.